Effects of physical training combined with transcranial direct current stimulation on maximal strength and lower limb explosive strength in healthy adults - Liu, Jintong; Li, Chunlei; Fang, Junhui; Xu, Haokai; Zhang, Xingyue; Zhao, Fan (Frontiers in Sports and Active Living, 2024)
Abstract Objective: The purpose of this systematic review and meta-analysis was to investigates whether transcranial direct current stimulation applied during physical training increases muscle strength in comparison with sham tDCS combined with physical training. Methods: Randomized controlled trials of the effects of tDCS combined physical training intervention on muscle strength and cortical excitability were collected by searching Web of Science, Pubmed, EBSCO, CNKI. The retrieval date ends in April 2024. 11 randomized controlled trials are finally included. The total sample size of the study is 338. The experimental group was subjected to tDCS combined with physical training intervention, and the control group was physical training combined with sham tDCS intervention. Results: There is a significant increase in maximal strength (SMD=0.38; 95%CI: 0.09, 0.67; p=0.01) and lower limb explosive strength (MD=2.90; 95%CI: 1.06, 4.74; p=0.002) when physical training was performed with tDCS, but not following physical training combined with sham tDCS. Subgroup analysis of the subject population showed an increase in muscle strength in those with training experience following tDCS combined with physical training (SMD=0.39; 95% CI: 0.08, 0.70; p=0.01), but not for those without training experience (SMD=0.29; 95% CI: -0.06, 0.63; p=0.10). Motor evoked potential (MEP) wave amplitude increased significantly following physical training with tDCS (SMD=0.71; 95%CI: 0.18, 1.24; p=0.008), but was not different between groups (SMD=0.16; 95%CI: -0.33, 0.65; p=0.52). Conclusions: tDCS combined with physical training intervention can improve muscle strength, lower limb explosive strength and cerebral cortex excitability. Compared to tDCS combined with training of small muscle groups, tDCS combined with training of large muscle groups was more effective in improving muscle strength. Muscle strength was more likely to improve after tDCS combined with physical training in people with physical training experience compared with people without physical training experience. The combination of tDCS with physical training intervention and the sham-tDCS with physical training intervention both increased cortical excitability.